Penumbuhan Film SnO2 Dengan Doping Al-Zn Menggunakan Teknik Sol-Gel Dip Coating - Norma Ikraman; Aris Doyan; Susilawati Susilawati (Department of Physics Education, Universitas Mataram, 2017)
Al-Zn doped SnO2 (Sn1-2xAlxZnxO2) film has been growth using the sol-gel dip coating technique. The basic materials used in this study were water, C2H5OH, SnCl2.2H2O, AlCl3 and ZnCl2 with 99% purity (merck) with doping concentration variation x = 0.000, 0.005, 0.025, and 0.050. Glass substrate with size 2.54 mm x 76.2 mm x 1 mm cleaned with detergent, soaked in 30% HCl solution For 1 day and dried at 100ÃÂ°C. The process of making a SnO2 sol is done by mixing the precursor with various concentrations with water and stirring using a magnetic stirrer for 30 minutes at a temperature of 80 ÃÂ° C. The next step by adding ethanol, stirring at 80 ÃÂ° C. for 2 hours to obtain 0.4 M sol solution The deposition of SnO2 film was carried out using a dip coater with a whitdrawl speed 12 cm/min and then heated for nucleation and grown using an electric furnace at 600 ÃÂ° C for 30 minutes. This step is repeated as much as 5 repetitions to get the SnO2 film by doing Al-Zn.